IMPLEMENTATIONS OF CORPORATE FARMING AND DEVELOPMENT OF BEAN CULTIVATION AT MAX YASA COOPERATIVE DISTRICT PURBALINGGA CENTRAL JAVA - Herlyna Novasari Siahaan (Journal of Agri Socio Economics and Business, 2023)
Horticulture is one of the potential agricultural sub-sectors. Max Yasa Cooperative is a primary cooperative that produces local chickpeas and Kenyans that export chickpeas to Singapore by establishing a farmer corporation system. This study aims to determine the application of corporate farming carried out by the Max Yasa Cooperative and to determine the strategy for developing a bean cultivation business using the Business Model Canvas (BMC) at the Max Yasa Purbalingga cooperative. The data in this study are primary data and secondary data. Data analysis techniques are carried out descriptively using the Business Model Canvas. The results showed that the application of corporate farming carried out by the Max Yasa Cooperative in terms of economy, society, and environment. Business Model Canvas as a model for developing cultivation business in max yasa purbalingga cooperative are (1) key partnership, namely export companies, and traders collecting local markets (2) key activities, namely providing agricultural production facilities, bean cultivation, post-harvest chickpea activities, and marketing of chickpeas (3) Key resources, namely partner farmer land, buildings for post-harvest activities, pickup cars as a means of transportation. (4) Customer segments, namely traders, collectors, and companies (5) Value proposition, namely the number of chickpea quotations (6) Channels consist of direct cooperation and contractual cooperation (7) Customer relationship, namely maintaining communication and maintaining product quality (8) revenue stream, namely sales of local chickpea products and Kenyan chickpeas (9) cost structure consists of production costs and labor wage costs.